Tailoring University Counselling Services to Aboriginal and International Students: Lessons from Native and International Student Centres at a Canadian University - Robertson, Lloyd Hawkeye; Holleran, Kathryn; Samuels, Marilyn (Canadian Journal of Higher Education, 2015)
<!-- [if gte mso 9]> <![endif]--> Critics have suggested that the practice of psychology is based on ethnocentric assumptions that do not necessarily apply to non-European cultures, resulting in the underutilization of counselling centres by minority populations. Few practical, culturally appropriate alternatives have flowed from these concerns. This paper reviews experiences from a doctoral-level practicum in counselling psychology that targeted aboriginal and international university students outside of the mainstream counselling services at a western Canadian university over a two-year period. It recommends an integrated approach, combining assessment, learning strategy skills, and counselling skills while incorporating community development methodology. The paper concludes with recommendations for counsellor training that will enhance services to both international and aboriginal students. <!-- [if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->